Influence of Users behaviour to IPTV service - Adomkus, T.; Bruzgiene, R.; Narbutaite, L. (Elektronika ir Elektrotechnika, 2012)
TV channel transmission of interactive IPTV service and the channel zapping process are influenced by users searching and viewing behaviour. The model of users behaviour influence to IPTV service and reliance on IPTV channel transmission are presented. The users IPTV channel selection from offered number of TV channels was evaluated. Estimated dependence on quantity of IPTV users to IPTV transmission method and network bandwidth settings. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2641